FORMATION OF AN EFFECTIVE MODEL OF FAMILY FARMING IN THE FIELD OF DAIRY FARMING - HUMENYUK, Vladyslav; KARPENKO, Vitalii; ANDRUSHKO, Vitaly (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive examination of the organizational and economic foundations for developing an effective model of family farming in the dairy cattle sector, taking into account contemporary challenges, the specific characteristics of Ukraine’s agricultural sector, and international experience. The evolution of family farming models within the milk market is analyzed, with key factors identified that determine their viability and competitiveness: farm size, technological equipment, access to financing, cooperation, and integration into value chains. A comparative analysis is conducted of dairy farming models in European Union countries (Germany, Poland, the Netherlands), where family farms dominate the market due to strong government support, stable political and economic conditions, and a high level of institutional organization.In contrast, milk production in Ukraine is largely based on small-scale household farms, which account for over 70% of total milk output but mostly operate outside the formal market system. The necessity of transforming these farms into full-fledged family farms with legal status is substantiated. Such transformation would enable integration into formal trade, improvement in product quality, and access to state support mechanisms, affordable credit programs, service infrastructure, and professional training.Particular attention is given to the risks accompanying the development of family dairy farming: market instability, price volatility, limited access to infrastructure, and the absence of effective market cooperation mechanisms. The study emphasizes the growing relevance of implementing innovative solutions, including digital platforms for accounting and sales, mobile herd management applications, and robotic milking systems. A conceptual model of an efficient family dairy farm is proposed, incorporating adaptive resource management, technological modernization, regional cooperation, and partnerships with the state through the implementation of comprehensive support instruments.The study concludes that the development of family farming in the dairy sector can serve as a foundation for the structural transformation of Ukraine’s dairy industry, contributing to food security, job creation in rural areas, the preservation of social cohesion in communities, and the sustainable development of the agricultural sector as a whole.
Keywords: family farming; dairy cattle farming; cooperation; agricultural policy; food security; transformational economy; agri-tech; rural development; effective model; digitalization